2021
DOI: 10.3389/fpsyt.2020.590343
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Anxiety, Depression, and Sleep Problems Among Caregivers of People Living With Neurocognitive Disorders During the COVID-19 Pandemic

Abstract: Objectives: To estimate the prevalence of anxiety, depression, and sleep problems among caregivers of persons living with neurocognitive disorders (PLWND) during the COVID-19 pandemic in China and investigate whether the COVID-19-related experiences were associated with the presence of anxiety, depression, and sleep problems.Methods: From March 1 to 31, 2020, 160 caregivers of PLWND participated in an online cross-sectional survey on the prevalence of anxiety, depression, and sleep problems. The 7-item General… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 30 publications
(34 reference statements)
1
32
1
Order By: Relevance
“…In addition to fear, the caregivers in our study also described having psychosomatic symptoms such as sadness, poor concentration, unhappiness, anger, insomnia, and guilt. The prevalence of sleep problems among caregivers of older adults with neurocognitive disorders during the COVID-19 period was found to be 9.4–10.8%, which is lower than in the present study [ 49 , 50 ].…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…In addition to fear, the caregivers in our study also described having psychosomatic symptoms such as sadness, poor concentration, unhappiness, anger, insomnia, and guilt. The prevalence of sleep problems among caregivers of older adults with neurocognitive disorders during the COVID-19 period was found to be 9.4–10.8%, which is lower than in the present study [ 49 , 50 ].…”
Section: Discussioncontrasting
confidence: 90%
“…Wimberly et al [42] reported in their study that 77% of caregivers of childhood cancer survivors had increased feelings of anxiety due to the outbreak. Nearly half (46.8%) of caregivers of older people with neurocognitive disorders were found to have anxiety during the COVID-19 pandemic [49,50]. Some studies have evaluated fear in caregivers of PWC during the pandemic, and one group reported detecting psychological distress in 46.5% of long-term caregivers [51].…”
Section: Discussionmentioning
confidence: 99%
“…However, family caregiver restrictions to entering congregate care settings changed with wave two and wave three of the COVID-19 pandemic and depended on the facility. Anxiety, burden, and loneliness increased [25,[33][34][35][36]. Family caregivers' perspectives on what they thought would have helped them and what supports are needed to support family caregivers now and in the future are reported in the Results section.…”
Section: Impacts Of the Covid-19 Pandemic On Family Caregiversmentioning
confidence: 99%
“…In fact, despite the fact that care providers differ in their working style, motivations, and aims between formal and informal caregivers, COVID-19 brought about overlapping responsibilities and a shift in roles that led both populations of caregivers to experience increased and imbalanced care distribution that negatively affected their mental well-being [ 33 , 34 ]. They were not only exposed to higher levels of stress, anxiety, and depression [ 35 , 36 ], but also equally revealed sleep disturbances [ 37 ], frustration, and hopelessness during their caregiving roles, with the consequent risk of struggling with negative emotions, such as self-criticism and shame [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%